(untitled) (Revista de Design, Tecnologia e Sociedade, 2018)
This paper described the path of Vila Rosario project that had its roots in empathic design, but finally built on Paulo Freire’s Pedagogy of the Oppressed. The study was conducted in 2005-2008 in Vila Rosario about 20 km north of downtown Rio de Janeiro. It focused on the prevention and treatment of tuberculosis. The paper describes our design approach, process, drivers, many design outcomes, and our tests. It ends with a discussion of the implications of our approach to design.